Morphological Characteristics of Kecombrang (Etlingera elatior (Jack) R. M. Smith) in Several Regions in Aceh Province, Sumatra - Rayhannisa Rayhannisa; Zumaidar Zumaidar; Amalia Amalia; Widya Sari; Saudah Saudah (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2024)
AbstractKecombrang (Etlingera elatior) is one of the plant species of the Zingiberaceae family is widely used by the community as food and medicine. Not much research has been done on the morphological diversity of kecombrang plants in Aceh, so scientific information about these plants is still minimal. Therefore, this research needs to be carried out to enrich knowledge about these plants in the Aceh region. Sampling was conducted from January to April 2022 at three places in Central Aceh, Banda Aceh, Weh Island, and Simeulue Island. This research was carried out according to the survey method by roaming and direct collection. A total of 12 groves were collected from wild and cultivated area and observed for 43 characters consisting of quantitative and qualitative data. Based on these observations, two variations of the kecombrang plant have been found based on the color of the bracts, namely the red and pink variants. Based on morphological characters of vegetative organs, all samples of Etlingera elatior had a similarity distance coefficient from 67 to 86%. In addition, the kecombrang plants found in the highlands of Central Aceh have a larger size in leaf and inflorescent compared to samples from other locations.AbstrakKecombrang (Etlingera elatior) adalah salah satu jenis tumbuhan famili Zingiberaceae yang secara luas penggunaanya dikenal oleh masyarakat sebagai makanan dan obat. Belum banyak penelitian terkait keanekaragaman morfologi tumbuhan kecombrang di Aceh, sehingga informasi ilmiah tentang tumbuhan ini masih sedikit. Oleh karena itu penelitian ini perlu dilakukan untuk memperkaya pengetahuan tentang tumbuhan tersebut di daerah Aceh. Pengambilan sampel dilakukan pada bulan Januari hingga April 2022 di tiga tempat yaitu di Aceh Tengah, Banda Aceh, Pulau Weh, dan Pulau Simeulue. Penelitian ini dilakukan dengan metode survei dengan cara jelajah dan pengumpulan langsung. Sebanyak 12 rumpun dikumpulkan dari kawasan liar dan budi daya dan diamati sebanyak 43 karakter yang terdiri dari data kuantitatif dan kualitatif. Berdasarkan pengamatan tersebut, ditemukan dua variasi tanaman kecombrang berdasarkan warna braktea, yaitu varian merah dan merah jambu. Berdasarkan karakter morfologi organ vegetatif, seluruh sampel Etlingera elatior memiliki koefisien kemiripan dari 67 hingga 86%. Selain itu, kecombrang yang ditemukan di dataran tinggi Aceh Tengah mempunyai ukuran daun dan perbungaan yang lebih besar dibandingkan sampel dari lokasi lain.